Reclamation of Sand Dunes in Rajasthan - Prakash, Mahendra (Indian Forester, 1957)
The article describes the different methods of afforestation of inland sands followed in various countries. Although the climatic conditions of Western Rajasthan, 70 per cent of which is the 'desert', are acute, afforestation is not an impossibility, due to availability of moisture and nutrition in the dunes. Processes of initial binding of shifting sands are explained, as also different methods and species used for immobilization and afforestation of sand-dunes in different ranges of annual precipitation. The success attained during the past four years of experimentation indicates that afforestation of dune areas is both practical and of economic importance.